12‐band k · p model for dilute bismide alloys of (In)GaAs derived from supercell calculations. Issue 4 (11th February 2013) - Broderick, Christopher A.; Usman, Muhammad; O'Reilly, Eoin P.
Abstract Incorporation of bismuth (Bi) in dilute quantities in (In)GaAs has been shown to lead to unique electronic properties that can in principle be exploited for the design of high efficiency telecomm lasers. This motivates the development of simple models of the electronic structure of these dilute bismide alloys, which can be used to evaluate their potential as a candidate material system for optical applications. Here, we begin by using detailed calculations based on an sp3s* tight‐binding model of (In)GaBixAs1 − x to verify the presence of a valence band‐anticrossing interaction in these alloys. Based on the tight‐binding model the derivation of a 12‐band k · p Hamiltonian for dilute bismide alloys is outlined. We show that the band structure obtained from the 12‐band model is in excellent agreement with full tight‐binding supercell calculations. Finally, we apply the 12‐band model to In0.53Ga0.47BixAs1 − x and compare the calculated variation of the band gap and spin–orbit‐splitting to a variety of spectroscopic measurements performed on a series of MBE‐grown In0.53Ga0.47BixAs1 − x/InP layers.